ENKRIPSI DATA PADA GAME SMARTPHONE SIMULASI HIDUP BERSIH DAN SEHAT MENGGUNAKAN UCS TRANSFORMATION FORMAT 8 - Geraldi R Wiwono; Marlina; Izmy Alwiah Musdar (KHARISMA Tech, 2022)
This study aims to encrypt user saved data on a Smartphone Game Simulasi Hidup Bersih dan Sehat with UCS Transformation Format 8 using C# language on Unity and Visual Studio 2019 platforms. The method used in this study is an experimental method for encryption and decryption of user stored data. in the form of name (string), score (float), total score (float), lives (float), and unlocked categories (float). The results of this study indicate that the created encryption and decryption codes have run optimally. The stored data has been successfully encrypted so that the data cannot be seen and read by unauthorized parties. The size of the encrypted data store increased by about 105-110 bytes.